The prognostic value of the urokinase-plasminogen activator system (uPA) in bladder cancer patients treated with radical cystectomy (RC) - Janisch, Florian; D'Andrea, David; Iwata, Takehiro; Kimura, Shoji; Abufaraj, Mohammad; Enikeev, Dmitry; Glybochko, Petr V; Karakiewicz, Pierre I; Nyirady, Peter; Fajkovic, Harun; Haitel, Andrea; Seebacher, Veronika; et al. (Urologic oncology, 2020)
PURPOSE: Urokinase-plasminogen activator (uPA), its receptor (uPAR), and the plasmin-activator inhibitor type 1 (PAI-1) have been associated with oncologic outcomes in various malignancies and could help identify bladder cancer (BC) patients treated with radical cystectomy (RC) who are likely to benefit from intensification of therapy to prevent disease progression. Our aim was to assess the value of uPA, uPAR, and PAI-1 for prognosticating survival outcomes of patients treated with RC for BC. MATERIALS AND METHODS: Tumor specimens from 272 consecutive patients treated with RC for advanced BC were assessed with immunohistochemical staining for uPA, uPAR, and PAI-1. Overexpression was assessed by pathological image analysis. Kaplan-Meier estimates and multivariable Cox-regression were used to analyze survival. Harrell's C-index was used to assess for clinical impact of the uPA system. RESULTS: uPA, uPAR, and PAI-1 were overexpressed in 48.2%, 51.1%, and 52.2% of patients, respectively. uPA overexpression was associated with lymphovascular invasion (P = 0.034) and nodal status (P = 0.013); PAI-1 overexpression was associated with primary muscle-invasive BC (P = 0.015) and lymphovascular invasion (P = 0.024). uPA, uPAR, and the number of overexpressed markers were all 3 significantly associated with shorter overall recurrence-free-, distant recurrence-free-, and cancer-specific survival. In multivariable analyses, uPA overexpression remained associated with shorter recurrence-free survival (hazard ratio [HR] = 1.79; P = 0.036) in the entire cohort, in patients without lymph node metastasis (HR = 1.98; P = 0.018) and those with nonorgan-confined disease (HR = 1.98; P = 0.022). uPAR overexpression was associated with shorter recurrence-free survival in patients without lymph node metastasis (HR = 2.01; P = 0.021) and those with organ-confined disease (HR = 4.11; P = 0.037). CONCLUSION: Members of the uPA system are associated with features of biologically aggressive BC and oncologic outcomes. However, their value beyond currently available information remains limited.
Keywords: senioři; Radical cystectomy; uPAR; Retrospective Studies; nádory močového měchýře; Prognosis; Bladder cancer; Cohort Studies; PAI-1; Middle Aged; mužské pohlaví; aktivátor plazminogenu urokinázového typu; Cystectomy; míra přežití; Receptors, Urokinase Plasminogen Activator; kohortové studie; uPA; ženské pohlaví; prognóza; receptory urokinázového aktivátoru plazminogenu; retrospektivní studie; Humans; Urokinase-Type Plasminogen Activator; Survival Rate; lidé středního věku; inhibitor aktivátoru plazminogenu 1; Plasminogen Activator Inhibitor 1; Urinary Bladder Neoplasms; Female; Aged; lidé; Male; cystektomie